Signaling in Fibrosis: TGF-β, WNT, and YAP/TAZ Converge - Piersma, Bram; Bank, Ruud A.; Boersema, Miriam (Frontiers in Medicine, 2015)
Chronic organ injury leads to fibrosis and eventually organ failure. Fibrosis is characterized by excessive synthesis, remodeling and contraction of extracellular matrix produced by myofibroblasts. Myofibroblasts are the key cells in the pathophysiology of fibrotic disorders and their differentiation can be triggered by multiple stimuli. To develop anti-fibrotic therapies, it is of paramount importance to understand the molecular basis of the signaling pathways contributing to the activation and maintenance of myofibroblasts. Several signal transduction pathways such as TGF-β, Wnt, and more recently YAP/TAZ signaling, have been linked to the pathophysiology of fibrosis. Activation of the TGF-β1-induced SMAD complex results in the upregulation of genes important for myofibroblast function. Similarly, Wnt-stabilized β-catenin translocates to the nucleus and initiates transcription of its target genes. YAP and TAZ are two transcriptional co-activators from the Hippo signaling pathway that also rely on nuclear translocation for their functioning. These three signal transduction pathways have little molecular similarity but do share one principle: the cytosolic/nuclear regulation of its transcriptional activators. Past research on these pathways often focused on the isolated cascades without taking other signaling pathways into account. Recent developments show that parts of these pathways converge into an intricate network that governs the activation and maintenance of the myofibroblast phenotype. In this review we discuss the current understanding on the signal integration between the TGF-β, Wnt, and YAP/TAZ pathways in the development of organ fibrosis. Taking a network wide view on signal transduction will provide a better understanding on the complex and versatile processes that underlie the pathophysiology of fibrotic disorders.